Over expression and application of the -carboxyltransferase (EgaccD) gene in oil palm (Elaeis guineensis Jacq) - Alisa Nakkaew; Amornrat Phongdara; Theera Eksomtramage; Wilaiwan Chotigeat (Songklanakarin Journal of Science and Technology (SJST), 2014)
Oil palm is an economic crop with its oil currently in high demand. In this work, the numbers of EgaccD copies, one of the key genes involved in fatty acid synthesis and oil production, were compared from two populations of oil palm, one a low and the other a high oil content productivity cultivar. Real time PCR was employed and the copy number of the EgaccD from the high oil yielding cultivar was much higher than from the low oil yielding cultivar. The EgaccD was then over expressed in oil palm calli under the control of its promoter to establish if its overexpression could enhance the oil content of transgenic calli. An increase in the lipid accumulation by the modified calli was detected by Sudan black B staining. Based on this finding, genetic manipulation of EgaccD seemed to be one promising method to try to increase the oil content. Also it seemed possible to use the level of this gene as a marker to assist selection of possible high oil yielding cultivars in breeding programs.